School-Bus Taking for Students with Disabilities: Who's On-Board?. Issue 3 (May 2023) - Gottfried, Michael A.; Ozuna, Christopher S.; Lloydhauser, Michael L.
Taking the school bus has long been an integral part of the school experience in the U.S. However, not much is known about how school transportation relates to getting to school each day, particularly for students with disabilities. This study used ECLS-K: 2011 to explore two issues. First, we examined what characteristics are associated with taking the school bus, comparing students with and without disabilities. Second, we evaluated the link between taking the school bus and absenteeism for these groups. In the first set of findings, school bus taking is differentiated by student and family characteristics, as well as by urbanicity. We find no major differences in characteristics associated with taking the bus between students with disabilities and students without. As for the second set of findings, students with more common disability diagnoses had fewer absences compared to both students without disabilities as well as those with lower incidence diagnoses, suggesting that taking the bus is related to better attendance behaviors for some students with disabilities. Implications are discussed.